Pendampingan Guru dalam Implementasi Model Pembelajaran Berbasis STEAM di PAUD Kapenewon Cangkringan - Ratri Nuria (Elsalima (Salam Institute), 2024)
The STEAM-based learning approach has proven to be effective in improving education quality. However, its implementation in madrasahs still faces various challenges, including limited teacher understanding and a lack of infrastructure support. This mentoring program aims to bridge these gaps by guiding teachers in effectively applying the STEAM model. This study focuses on three main aspects: the mentoring process, factors influencing the effectiveness of implementation, and the impact of mentoring on teaching quality and student competence. The community service method involved workshops and seminars attended by PAUD teachers in Cangkringan. The program included training on STEAM concepts, classroom implementation practices, and evaluations of the applied methods' effectiveness. The findings indicate an improvement in teachers’ understanding and skills in applying STEAM, resulting in increased student engagement, creativity, and critical thinking skills. Additionally, supporting factors such as school policies and the availability of facilities played a crucial role in the successful implementation. With these positive results, this program is expected to serve as a model for other madrasahs in adopting STEAM-based learning.